2020
DOI: 10.1021/acs.joc.0c02441
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polysubstituted Isoindolinones via Radical Cyclization of 1,3-Dicarbonyl Ugi-4CR Adducts Using Tetrabutylammonium Persulfate and TEMPO

Abstract: The development of an efficient method for the synthesis of polysubstituted isoindolinones from 1,3-dicarbonyl Ugi-4CR adducts, employing an aromatic radical cyclization process promoted by tetrabutylammonium persulfate and 2,2,6,6-tetramethyl-1-piperidine 1-oxyl (TEMPO), is described. The protocol allowed the construction of a library of isoindolinones bearing a congested carbon in good to excellent yields under mild conditions and in short reaction times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 87 publications
0
24
0
2
Order By: Relevance
“…The benzamide core is widespread in biologically relevant compounds, including antitumor agents, antidepressants, and recently inhibitors of SARS-CoV-2 replication, which renders the functionalization of this structure a vibrant area of research. , While different strategies targeting the aromatic ring or the carbonyl group of benzamides are well developed, , the repertoire of methods for direct transformations at the N -unit remains limited (Scheme a, right). To overcome this challenge, several indirect approaches have been investigated. They typically involve reductive activation of the aromatic carbon–halide bond at the position ortho to the carbonyl group, followed by intramolecular 1,5-hydrogen-atom transfer (1,5-HAT), giving access to reactive species at a position α to the N -atom (Scheme b). Although they are highly efficient, these methods necessitate strongly reducing reagents or specific catalysts, thereby restricting the available chemical space to radical reactivityparticularly radical cyclizationand precluding the possibility of more general, divergent strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The benzamide core is widespread in biologically relevant compounds, including antitumor agents, antidepressants, and recently inhibitors of SARS-CoV-2 replication, which renders the functionalization of this structure a vibrant area of research. , While different strategies targeting the aromatic ring or the carbonyl group of benzamides are well developed, , the repertoire of methods for direct transformations at the N -unit remains limited (Scheme a, right). To overcome this challenge, several indirect approaches have been investigated. They typically involve reductive activation of the aromatic carbon–halide bond at the position ortho to the carbonyl group, followed by intramolecular 1,5-hydrogen-atom transfer (1,5-HAT), giving access to reactive species at a position α to the N -atom (Scheme b). Although they are highly efficient, these methods necessitate strongly reducing reagents or specific catalysts, thereby restricting the available chemical space to radical reactivityparticularly radical cyclizationand precluding the possibility of more general, divergent strategies.…”
Section: Introductionmentioning
confidence: 99%
“… [33] The initial step of the reaction involves a thermally‐induced homolytic cleavage of sodium persulfate to generate two equivalents of the sulfate radical anion (SO 4 −. ) [41–45] . This radical anion then oxidizes nitroxide 2 in a single‐electron transfer (SET) process to the oxoammonium cation 1 which then performs the oxidative amidation reaction via the intermediacy of an acyl pyridinium ion [21,24,46] and, in so doing, generating hydroxylamine 3 .…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, Polindara-García et al reported the synthesis of isoindolines via an intramolecular radical cyclization of 1,3-dicarbonyl compounds, which was derived from the Ugi reaction. 233 TEMPO + oxidizes the in-situ generated cyclohexadienyl radical intermediate and their subsequent aromatization yielded the desired product. Recently, a new activity of oxoammonium species has been discovered, which was reported by some researchers but not fully investigated until 2021.…”
Section: -8-3 Other Oxidative Transformations (Scheme 38)mentioning
confidence: 99%